Models and Determinants of International Tourism Demand: perspectives from the Systematic Literature Review for the period 2000-2020 - Camara, Isabela Lima Pinheiro da (2022)
Understanding the evolution process of methodologies and the use of variables that explain tourism demand has been a relevant concern in the specialized literature. Some bibliometric studies sought to understand this evolution process: Johnson and Ashworth (1990); Li, Song and Witt (2005) and Song, Qui and Park (2019). Most of these studies have focused on discussing the evolution and efficiency of the models used in the analysis and forecasting of demand, paying little attention to the variables. This article contributes to this discussion, evaluating the relationship between the models used in the literature and variables used in the analysis of tourism demand. For this, a bibliometric study was carried out in the main international research bases: Web of Science, Redalyc, Scielo, Spell and Publicações de Turismo, between 2000 and 2020 (March) seeking to answer two questions: 1. Is there any relationship between the selection of models and the set of variables used in the analysis of tourism demand? 2. Are there any trends in using new variables? The study found that, regardless of the model used, the variable number of arrivals has been more used to represent tourism demand. It was also observed that the independent variables income, price and exchange rate were the most used and that there is a tendency to incorporate new variables